The impact of supervisor bottom-line mentality on employees’ knowledge hiding: The mediating role of performance avoidance orientation and the moderating role of self-efficacy - Du, Hongchun; Chen, Chun-shuo (Edelweiss Applied Science and Technology, 2026)
In the era of the digital economy, the competitive advantage of internet enterprises is gradually shifting to knowledge-based intangible assets. However, leaders’ behaviors and cognitive patterns, especially the prevalence of supervisor bottom-line mentality, have severely hindered internal knowledge flow. This study aims to explore the impact of supervisor bottom-line mentality on employees’ knowledge hiding. By conducting a quantitative study that takes performance avoidance orientation as the mediating variable and self-efficacy as the moderating variable, empirical data were collected from the internet industry via a questionnaire survey. A total of 733 questionnaires were retrieved, with 503 valid samples and an effective response rate of 68.6%. Data analysis results show that supervisor bottom-line mentality strengthens performance avoidance orientation; performance avoidance orientation exacerbates knowledge hiding; performance avoidance orientation plays a partial mediating role between supervisor bottom-line mentality and knowledge hiding; self-efficacy significantly reduces the impact of supervisor bottom-line mentality on performance avoidance orientation. This finding provides theoretical support for managers to recognize the potential consequences and negative impacts of bottom-line mentality and to construct an open and collaborative organizational culture.